2021
DOI: 10.3390/d13020096
|View full text |Cite
|
Sign up to set email alerts
|

The Diverse Assemblage of Fungal Endophytes from Orchids in Madagascar Linked to Abiotic Factors and Seasonality

Abstract: The inselbergs of the Central Highlands of Madagascar are one of many ‘micro-hotspots’ of biodiversity on the island, particularly for Orchidaceae. In this region are several genera that have a large number of endemic species that are in serious decline or edging towards extinction. Studies relating to diversity of orchids and their fungal partners (both mycorrhizal and non-mycorrhizal root associates) deserve more attention, as climate change and human induced decline in resilience of species in the wild is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…Therefore, for the purpose of understanding specific requirements for reintroduction, targeted environmental analysis is required. Previous studies indicate that low P content may be linked to higher mycorrhizal diversity in Cephalanthera rubra [40] and several orchids from Madagascar [11]. Likewise, Van der Ent et al [41] found that the rhizosphere soil concentrations of P and K was low in soil in the study site where Paphiopedilum rothschildianum was growing.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Therefore, for the purpose of understanding specific requirements for reintroduction, targeted environmental analysis is required. Previous studies indicate that low P content may be linked to higher mycorrhizal diversity in Cephalanthera rubra [40] and several orchids from Madagascar [11]. Likewise, Van der Ent et al [41] found that the rhizosphere soil concentrations of P and K was low in soil in the study site where Paphiopedilum rothschildianum was growing.…”
Section: Discussionmentioning
confidence: 77%
“…About 10% of all angiosperm species are orchids which are associated with roughly 25,000 Basidiomycota and some Ascomycota as fungal partners [36,37]. These associations are guided by soil characteristics, seasonality, and life forms of the orchids [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As this site is hosting a diverse range of orchids seed-germination-compatible Tulasnella OTU from southern marsh orchid (from a chalky wet habitat) was tested among many other isolates of putative mycorrhizal fungi for yellow early marsh. The lineage of Tulasnellaceae, a common mycorrhizal fungus in orchids shows generalist behavior as reported in many Dactylorhiza and other terrestrial orchids [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 90%
“…The current study used fungi available from plants at different growth phases and found that Tulsanella OTU from mature phase D. praetermissa was a germination-compatible fungus. This has been proved as a successful approach in identifying putative mycorrhizal fungi in orchids from Madagascar [ 17 , 24 , 31 , 32 , 39 ]. Putative mycorrhizal fungus isolate from seedlings was more efficient at supporting seed germination compared to those isolated from adult roots in Dendrobium exile [ 38 , 40 ] suggested that the fungi used in conservation must be limited to mycorrhizal fungi acquired from the same or nearby populations.…”
Section: Discussionmentioning
confidence: 99%